Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan Penanganan Prasarana dan Sarana Umum (PPSU) pada Kantor Kelurahan Pesanggrahan Jakarta Selatan - Windy Gustia Wardani; Dira Karlina; Lily Setyawati Kristianti (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study is motivated by the importance of improving employee performance in public service units, particularly the Penanganan Prasarana dan Sarana Umum (PPSU) at the Pesanggrahan Subdistrict Office, South Jakarta. Employee performance is assumed to be influenced by internal factors such as motivation and work discipline, which play a critical role in achieving organizational effectiveness. The objective of this research is to examine the effect of motivation and work discipline on employee performance, both partially and simultaneously. This research employs a quantitative approach with an associative research method. The study involves 100 respondents selected using a census sampling technique. Data were collected through the distribution of Likert-scale questionnaires. The data were processed using SPSS version 29 and analyzed using multiple linear regression techniques to determine the relationship and influence between variables. The results indicate that motivation and work discipline have a positive and significant effect on employee performance, both individually and collectively. Work discipline shows a stronger influence compared to motivation, suggesting that adherence to rules and consistency in work behavior are key determinants of performance among PPSU employees.